Protein Defense Systems against the Lantibiotic Nisin: Function of the Immunity Protein NisI and the Resistance Protein NSR - Khosa, Sakshi; Lagedroste, Marcel; Smits, Sander H. J. (Frontiers in Microbiology, 2016)
Lantibiotics are potential alternatives to antibiotics because of their broad-range killing spectrum. The producer strain is immune against its own synthesized lantibiotic via the expression of two proteins LanI and LanFEG. Recently, gene operons are found in mainly human pathogenic strains, which confer resistance against lantibiotics. Of all the lantibiotics discovered till date, nisin produced by some L. lactis strains is the most prominent member. Nisin has multiple mode of actions of which binding to the cell wall precursor lipid II and subsequent insertion into the bacterial membrane to form pores are the most effective. The nisin producing strains express the lipoprotein NisI to prevent a suicidal effect. NisI binds nisin, inducing a reversible cell clustering to prevent nisin from reaching the membrane. Importantly NisI does not modify nisin and releases it as soon as the concentration in the media drops below a certain level. The human pathogen S. agalactiae is naturally resistant against nisin by expressing a resistance protein called SaNSR, which is a nisin degrading enzyme. By cleaving off the last six amino acids of nisin, its effectiveness is 100-fold reduced. This cleavage reaction appears to be specific for nisin since SaNSR recognizes the C-terminal located lanthionine rings. Recently, the structures of both NisI and SaNSR were determined by NMR and X-ray crystallography, respectively. Furthermore, for both proteins the binding site for nisin was determined. Within this review, the structures of both proteins and their different defence mechanisms are described.